Rationalization of Action in Education Investment Decisions: Parents' Perceptions - Andy Prasetyo Wati; Sri Handayani; Durinda Puspasari; Jefry Aulia Martha (Ekuitas: Jurnal Pendidikan Ekonomi, 2023)
This research aims to see how the rationality of parents towards their decision to act in improving the quality of human resources owned by children through education. This is due to the problems that arise from various theoretical studies on "Is the decision taken by parents in sending their children to school a rational action or is it only limited to the fulfillment of educational policies that have been made by the government in supporting the improvement of the quality of human resources through education?". Therefore, to answer the problems and objectives of this study, the researchers used a type of quantitative research with correlation and regression test methods. The research data was collected using a 7-point scale research instrument distributed through an online survey, and the data obtained was 185 respondents. The population and sample in the study were parents of students in class XII, Malang, East Java. The results of the study revealed that instrumental action rationalization and value action rationalization were able to significantly influence parents' decisions in investing in education. The hope of this research is more emphasized on the ability of parents to think rationally when making decisions to invest in children's education, especially on rational analysis of costs and benefits, and avoiding implicit or emotional decisions. Therefore, further research is needed on how parents respond to the decision to invest in education when viewed from other factors, both from internal parents and external factors from parents.